Unlocking the potential of de-oiled seeds of Citrus sinensis loaded with metal nanoparticles for Congo red degradation and removal: a green water treatment strategy with bibliometric analysis - Tahira, Misbah; Batool, Fozia; Noreen, Sobia; Mustaqeem, Muhammad; Munawar, Khurram Shahzad; Kanwal, Samia; Shahbaz, Komal; Arshad, Anila; Ali, Hayssam M. (Frontiers in Sustainable Food Systems, 2024)
This research reported the utilization of novel adsorbent from the de-oiled waste material of orange seeds to prepare simple charcoal (SC) and activated charcoal nanocomposites (Fe2O3/AC). Batch adsorption experiments were carried out to evaluate the optimized conditions of the experiment. The results obtained indicate that the Pseudo second-order kinetic model best fitted the adsorption data (R 2 > 0.99) and the Freundlich isotherm model best explained the adsorption of dye on Fe2O3/AC. Moreover, the adsorption process was spontaneous and exothermic in the temperature range of 293-333 °K as explained by calculated thermodynamic parameters e.g. ΔG°, ΔH°, and ΔS°. The FTIR results publicized that carboxyl and amine functional groups are present on the surface of adsorbent which are responsible for the attachment of dye. SEM results showed that Fe2O3/AC has a porous surface and textual structure which can efficiently adsorb the dye molecules. Zeta sizer was utilized for the determination of size of composites and thermal stability was determined by TGA analysis. Findings of the comparative experiment indicated that Fe2O3/AC are more promising as compared to raw activated carbon for the adsorption of Congo red. The impregnation of iron oxide nanocomposites on adsorbent results in increased surface area-to-volume ratio, magnetic properties, and excellent reusable capacity. Overall it can be reported as an innovative procedure promoting the recycling of waste products aiding in protecting environmental and human health and economic development.